2022
DOI: 10.3390/life12101579
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Possible Antioxidant, Anti-Hyperglycaemic, Anti-Alzheimer and Anti-Inflammatory Effects of Teucrium polium Aerial Parts (Lamiaceae)

Abstract: Teucrium polium L. is commonly used in folk medicine to treat hypertension and diabetes and to heal wounds. The present work aimed to evaluate the different biological activities of T. polium hydroalcoholic extract, its total phenol and flavonoid content, and its mineral elements. Results showed that T. polium extract showed significant antioxidant potential in 2-diphenyl-1-picrylhydrazyl (DPPH) assay with IC50 equal to 8.68 μg/mL but with moderate activity in galvinoxyl assay with IC50 of 21.82 μg/mL and mild… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 56 publications
1
5
0
Order By: Relevance
“…Briefly, our study confirmed previous findings reported by Boughalleb et al, [18] , Al-Saeghi et al, [28] Agour et al, [29] Sharifi-Rad et al, [30] Benchikha et al, [31] and Makhlouf-Gafsi et al [32] Generally, to assess the antioxidant potential of bioactive extracts, several factors are involved such as solvent polarity, extraction methods, plant matrix and especially phenolic compounds containing including caffeic acid, 4-feruloylquinic acid, flavonoids, alkaloids and carotenoids. [16,[33][34][35]…”
Section: Antioxidant Activitiessupporting
confidence: 92%
“…Briefly, our study confirmed previous findings reported by Boughalleb et al, [18] , Al-Saeghi et al, [28] Agour et al, [29] Sharifi-Rad et al, [30] Benchikha et al, [31] and Makhlouf-Gafsi et al [32] Generally, to assess the antioxidant potential of bioactive extracts, several factors are involved such as solvent polarity, extraction methods, plant matrix and especially phenolic compounds containing including caffeic acid, 4-feruloylquinic acid, flavonoids, alkaloids and carotenoids. [16,[33][34][35]…”
Section: Antioxidant Activitiessupporting
confidence: 92%
“…Depending on the concentration, other phenolic compounds such as catechin molecules also chelate with Fe 2+ ions in the aqueous environments [ 98 ]. Moreover, certain plant derivatives have been found to contain essential minerals with metal ions such as calcium, potassium, iron, sodium, zinc, and magnesium, which are vital to maintaining the body’s fluid and electrolyte balance [ 99 , 100 ].…”
Section: Novel Phyto-therapeutic Approaches In Admentioning
confidence: 99%
“…Several vitamins, such as B 6 , B 9 , K, C, and E help in decreasing oxidative stress and improving brain functions [ 12 ]. Additionally, some plant extracts possess potential anti-AD properties, such as Punica granatum [ 13 ], Teucrium polium [ 14 ], Fragaria ananassa [ 15 ], Bacopa floribunda [ 16 ], and Ginkgo biloba [ 17 ]. On the other hand, Abelmoschus esculentus L., synonym: Hibiscus esculentus , mostly identified as okra or lady´s fingers, is a nutrient-rich food.…”
Section: Introductionmentioning
confidence: 99%